A phenomenological approach to profiling the life experiences of the Kayayoo in Ghana - Dodd, Rose Aba (Graduate School of Development Policy and Practice, 2022)
The Kayayei of Ghana have been studied over several decades though there still exists a gap in the literature based on their profiles. A contributing factor to that gap is the limited information around how many Kayayoo are across the country. Another is the varied demographic and biographic profiles of Kayayoo that provide a good extent of diversity but not depth. Current policy and program interventions are driven by the profiles of Kayayoo, as is presented in existing research. However, the existing profiles miss out on the richness and texture of the Kayayoo's life, which means that programs and policy interventions that use them are not as effective as they could be in reaching the Kayayoo's needs. This phenomenological study revealed that there is likely no need to continue trying to conduct a census of Kayayoo in other to understand their lives. Especially since the nature of their movements in migration remain nomadic. Instead, what is needed are interventions on their external environment that will strengthen their sense of choice and agency. This study's insights show that the meaning and connections the Kayayoo constructs of family, social network, and work are driven by their construction of self. It showed that the Kayayoo exercises more of their agency than may be evident. Their actions are engendered by what they perceive allows them to exercise this agency and choice. With this insight, what is needed is a mapping of the Kayayoo's external environment to identify their intersections with public policy and other services, and then design interventions on that environment to maximize the benefits of their actions when they make a choice to access it. The outcomes of policy and programs will undoubtedly be better and more impactful if designed based on this more in-depth understanding of the Kayayei from their point of view.